2021
DOI: 10.3390/jcm10214839
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for COVID 2019-Acute Respiratory Distress Syndrome: Comparison between First and Second Waves (Stage 2)

Abstract: We aimed to compare the outcomes of patients under veno-venous extracorporeal membrane oxygenation (V-V ECMO) for COVID-19-Acute Respiratory Distress Syndrome (CARDS) between the first and the second wave. From 1 March 2020 to 30 November 2020, fifty patients requiring a V-V ECMO support for CARDS were included. Patient demographics, pre-ECMO, and day one, three, and seven on-ECMO data and outcomes were collected. The 90-day mortality was 11% higher during the second wave (18/26 (69%)) compared to the first wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 47 publications
0
17
1
Order By: Relevance
“…In this study, the mean duration of ECMO support in patients with ARDS was 1.6 days (SD 2.8), which was relatively short compared to that observed in previous reports 15 , 16 . The difference might be due to the characteristics of patients who underwent ECMO support.…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, the mean duration of ECMO support in patients with ARDS was 1.6 days (SD 2.8), which was relatively short compared to that observed in previous reports 15 , 16 . The difference might be due to the characteristics of patients who underwent ECMO support.…”
Section: Discussioncontrasting
confidence: 59%
“…Data from the EuroECMO survey demonstrated increasing mortality with decreased weaning and survival in the second wave of the pandemic 13 . Similarly, an observational study in France demonstrated longer periods of noninvasive ventilation and worse pulmonary status before ECMO implantation 14 . In Germany, the overall hospital mortality also increased throughout the course of the pandemic 12 .…”
Section: Commentmentioning
confidence: 97%
“… 13 Similarly, an observational study in France demonstrated longer periods of noninvasive ventilation and worse pulmonary status before ECMO implantation. 14 In Germany, the overall hospital mortality also increased throughout the course of the pandemic. 12 A recent report published by the Extracorporeal Life Support Organization Registry (ELSO) found that in‐hospital mortality 90 days after ECMO initiation for COVID‐19 after May 1, 2020 was 52% compared to 37% before that date.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no differences between the three waves for the occurrence of thrombotic complication, major bleeding, heparin-induced thrombocytopenia, or the use of renal replacement therapy (Table 3). The median duration of ECMO support (24 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] days vs. 10 [8-21] days, p = 0.001) and ICU stay (36 [24-47] days vs. 26 [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], p = 0.008) were higher during the second wave. During their stay in ICU, 100% of the second and the third waves patients developed ventilator-associated pneumonia.…”
Section: Outcomementioning
confidence: 99%